2021
DOI: 10.1021/acsomega.1c04482
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Valent Iron Nanoparticles Induce Reactive Oxygen Species in the Cyanobacterium, Fremyella diplosiphon

Abstract: Nanoscale zero-valent iron nanoparticles (nZVIs) are known to boost biomass production and lipid yield in Fremyella diplosiphon, a model biodiesel-producing cyanobacterium. However, the impact of nZVI-induced reactive oxygen species (ROS) in F. diplosiphon has not been evaluated. In the present study, ROS in F. diplosiphon strains (B481-WT and B481-SD) generated in response to nZVI-induced oxidative stress were quantified and the enzymatic response determined. Lipid peroxidation as a measure of oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Apart from the anticancer activity of CAP, zero-valent iron nanoparticles (nZVI) have been identified with anticancer properties. The nZVI was originally developed to improve the magnetic properties of iron oxide-based NPs and use for the reduction of the pollutants in wastewater and environmental remediation [11,12], biological applications such as biodieselproducing cyanobacterium [13], and cytotoxicity effect on cancer cells [14][15][16][17]. Previous studies showed that nZVI increases ROS levels in cancer cell lines [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the anticancer activity of CAP, zero-valent iron nanoparticles (nZVI) have been identified with anticancer properties. The nZVI was originally developed to improve the magnetic properties of iron oxide-based NPs and use for the reduction of the pollutants in wastewater and environmental remediation [11,12], biological applications such as biodieselproducing cyanobacterium [13], and cytotoxicity effect on cancer cells [14][15][16][17]. Previous studies showed that nZVI increases ROS levels in cancer cell lines [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the stress could potentially impair the cellular machinery tasked with ATP synthesis, resulting in a significant decline in ATP yield. In a study by Gichuki et al [ 25 ], significant increases in dichlorofluorescein and malondialdehyde content, indicating oxidative stress in F. diplosiphon B481-SD subjected to nZVIs exceeding 3.2 mg/L, were reported. Another possible explanation could be attributed to the interference of nZVIs with the electron transport chain that is integral to photosynthesis, subsequently hampering ATP production [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zero-valent iron nanoparticles used in this study were obtained from Nano Iron company (Rajhrad, Czech Republic). These nZVIs have been previously characterized in our laboratory, and the average particle size determined to be approximately 53 nm [ 17 ]. Ampicillin, one of the β-lactam group antibiotics targeting cellular membranes, was used in this study.…”
Section: Methodsmentioning
confidence: 99%